Ste20‐like kinase activity promotes meiotic resumption and spindle microtubule stability in mouse oocytes. Issue 4 (29th December 2022) - Song, Ke; Jiang, Xiuying; Xu, Xiangning; Chen, Ye; Zhang, Jiaqi; Tian, Ying; Wang, Qian; Weng, Jing; Liang, Yuanjing; Ma, Wei
Abstract: Ste20‐like kinase (SLK) is involved in cell proliferation and migration in somatic cells. This study aims to explore SLK expression and function in mouse oocyte meiosis. Western blot, immunofluorescence, Co‐immunoprecipitation, drug treatment, cRNA construct and in vitro transcription, microinjection of morpholino oilgo (MO) and cRNA were performed in oocytes. High and stable protein expression of SLK was detected in mouse oocyte meiosis, with dynamic distribution in the nucleus, chromosomes and spindle apparatus. SLK phosphorylation emerges around meiotic resumption and reaches a peak during metaphase I (MI) and metaphase II. SLK knockdown with MO or expression of kinase‐dead SLK K63R dramatically delays meiotic resumption due to sequentially suppressed phosphorylation of Polo‐like kinase 1 (Plk1) and cell division cycle 25C (CDC25C) and dephosphorylation of cyclin‐dependent kinase 1 (CDK1). SLK depletion promotes ubiquitination‐mediated degradation of paxillin, an antagonist to α‐tubulin deacetylation, and thus destroys spindle assembly and chromosome alignment; these phenotypes can be substantially rescued by exogenous expression of SLK kinase active fragment. Additionally, exogenous SLK effectively promotes meiotic progression and spindle assembly in aging oocytes with reduced SLK. Collectively, this study reveals SLK is required for meiotic resumption and spindle assembly in mouse oocyte meiosis. Abstract : Around meiotic resumption in oocytes, SLK inspires a signal cascade involving Plk1, CDC25C and CDK1, therefrom bringing about metaphase‐promoting factor maturation, and during the following meiotic progression, promotes microtubule acetylation by regulating paxillin stability to ensure correct spindle assembly and chromosome alignment.